Potentiality of utilizing woven pineapple leaf fibre for polymer composites - Hadi, Agung Efriyo; Siregar, Januar Parlaungan; Cionita, Tezara; Norlaila, Mohd Bakeri; Muhammad Amin, Mohd Badari; Irawan, Agustinus Purna; Jamiluddin, Jaafar; Rihayat, Teuku; Ramli, Junid; Fitriyana, Deni Fajar (MDPI, 2022)
Pineapple leaf fibre (PALF) is one of the natural fibres with the highest tensile strength and cellulose content. This has led to the investigation of the application of short, long, random mats, and unidirectional types as reinforcement agents, but there is limited study on the usage of woven PALF in composites. Therefore, this study aims to investigate the potential of this woven PALF in reinforcing epoxy resin (ER) composite as well as the effect of layering numbers and fibre orientations on the mechanical properties of the product. This involved using hand lay-up and press moulding with a hydraulic machine to produce the composite and specimen test while 2, 3, and 4 layers of woven PALF were used as the layering number parameter. Moreover, the warp and weft direction of the woven PALF were used to simulate the effect of fibre orientation in composites. The findings showed that the 3-layer woven PALF performed better in terms of tensile and flexural properties than the other layers. It was also discovered that the orientation of the composite with warp direction is slightly higher than the weft direction. Furthermore, the scanning electron microscopic (SEM) method was applied to analyse the tensile fracture of the composites and the results showed that the interfacial adhesion of the 3-layer woven PALF successfully transferred the load to the epoxy resin matrix due to its reinforcement role in composites.